1991
DOI: 10.1029/90jb01432
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Middle Paleozoic sea level and tectonic events in cratonic margins and cratonic basins of North America

Abstract: The cratonic margins and basins of North America contain evidence of distinct changes in relative sea level, one of the most intriguing of which occurred in middle Paleozoic time. The change in relative sea level began in Frasnian time (Late Devonian) and continued through Visean time (Middle Mississippian) in the Cordilleran miogeocline, in the Southern Oklahoma Aulacogen, in the Appalachian miogeocline and in the Michigan, Illinois, and Williston basins. The synchroneity and wide geographic distribution of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 89 publications
1
23
0
Order By: Relevance
“…Wilson & Lyashkevich 1996), the reactivation of preexisting structures, far field effects, or changes in intraplate stress, may also occur. Subsidence analysis studies from North America have shown that the initiation of subsidence of the Illinois, Michigan and Williston basins, and the initiation of subsidence of latest Precambrian and earliest Palaeozoic passive margins were coeval with late Precambrian-age supercontinent break-up (Bond & Kominz 1991). A similar relationship between supercontinental break-up and intracontinental basin formation is also noted from the late Proterozoic of Australia (Lindsay & Korsch 1989) and the Mesozoic and Cenozoic of Europe and India (Klein & Hsui 1987).…”
Section: Intracratonic Rift Basinsmentioning
confidence: 66%
“…Wilson & Lyashkevich 1996), the reactivation of preexisting structures, far field effects, or changes in intraplate stress, may also occur. Subsidence analysis studies from North America have shown that the initiation of subsidence of the Illinois, Michigan and Williston basins, and the initiation of subsidence of latest Precambrian and earliest Palaeozoic passive margins were coeval with late Precambrian-age supercontinent break-up (Bond & Kominz 1991). A similar relationship between supercontinental break-up and intracontinental basin formation is also noted from the late Proterozoic of Australia (Lindsay & Korsch 1989) and the Mesozoic and Cenozoic of Europe and India (Klein & Hsui 1987).…”
Section: Intracratonic Rift Basinsmentioning
confidence: 66%
“…The rate of Devonian subsidence of the Illinois basin can be inferred by analyzing the thickness of sediments deposited dur ing specified time intervals, making suitable allowance for for changes in water depth and for compaction. According to Kominz and Bond (1990) and Bond and Kominz (1991), the apparent subsidence rate in the Illinois basin was fairly constant during Devonian time, and increased toward the end of the Devonian and through Mississippian time (Fig. 5).…”
Section: Epeirogenic Basins Domes and Archesmentioning
confidence: 89%
“…5). The increase in subsi dence rate at the end of the Devonian exceeds the estimated rate of eustatic sea-level rise, and thus must be the consequence of tectonic processes (Bond and Kominz, 1991). Deposition dur ing the Late Devonian and Early Mississippian yielded the New Albany Shale, an interval of black shale deposited under anaer obic conditions (Stevenson et al, 1981).…”
Section: Epeirogenic Basins Domes and Archesmentioning
confidence: 98%
See 1 more Smart Citation
“…Figure 3 shows the evolution of depth to basement, tectonic subsidence, and a thermal subsidence curve fit exclusively to pre-Black River Formations for seven deep wells in the Michigan Basin. Striking is the weakness of the long-term subsidence and the irregularity of the tectonic subsidence curve [Bond and Kominz, 1991]. Stretching factors [McKenzie, 1978] determined from these and other wells are all within the range cif 1.05-1.40.…”
Section: Estimating Tectonic Subsidencementioning
confidence: 96%